Multiattribute prediction of terrain stability above underground mining operations - Vujić, Slobodan; Miljanović, Igor; Milutinović, Aleksandar; Đorđević, Dragan; Gojković, Nebojša; Gajić, Grozdana (Yugoslav Journal of Operations Research, 2011)
This paper is dedicated to the problem of stability prediction of the terrain above underground mining operations. After the initial introduction to the problem, then the short analysis of the model approaches used to solve it, and giving the algorithm for rock massif stability prediction, we describe the concept of the multiattirbute terrain stability prediction method. The application of the multiattribute prediction method for stability of the terrain above underground mining operations is presented on the example of the Brown Coal Mine Aleksinac. The used method is original, essentially different from the other methods of mathematical modeling, because its prognosis of the rock massif stability under the influence of underground mining operations is based on the balance of the stability indicators. Our comparative analysis of the results obtained by multiattribute prediction and the data obtained by measurements of real deformations and terrain settling in multiple mines shows high mutual correlation, with an average deviation of less than ±10%. These results are confirmed entirely on the example of the Brown Coal Mine Aleksinac.